Exploring the Impact of Mobile Devices in E-Learning: A case Study Evaluating its Effectiveness - Ghoulam, Khalid; Bouikhalene, Belaid (Educational Challenges, 2024)
Aim. The integration of mobile devices into educational environments has revolutionized the landscape of e-learning, presenting new opportunities and challenges. This research paper aims to examine the pivotal role of mobile devices in the e-learning environment and assess the effectiveness of mobile learning applications in enhancing the educational experience. Methodology. The study employs a mixed-methods approach, combining quantitative data through surveys and usage analytics with qualitative insights derived from interviews and focus group discussions. Results. By analyzing the perspectives of both educators and learners, the research investigates how mobile devices contribute to the flexibility and accessibility of e-learning content. Additionally, the paper evaluates the effectiveness of various mobile learning applications in promoting engagement, knowledge retention, and overall learning outcomes. It scrutinizes the features that contribute to the success of these applications, such as user interface design, interactivity, and adaptability to diverse learning styles. Furthermore, the research delves into the challenges associated with mobile learning, including issues related to device compatibility, connectivity, and user motivation. Strategies to overcome these challenges and optimize the benefits of mobile learning are explored. The findings of this study are expected to provide valuable insights for educators, curriculum designers, and developers of mobile learning applications. Conclusion. The research contributes to the ongoing discourse on the effective integration of mobile devices in e-learning environments and offers recommendations for optimizing the design and implementation of mobile learning strategies.